2016
DOI: 10.1136/bmjopen-2016-011638
|View full text |Cite
|
Sign up to set email alerts
|

Substance-related and addictive disorders among adults with intellectual and developmental disabilities (IDD): an Ontario population cohort study

Abstract: ObjectivesDescribe the prevalence of substance-related and addictive disorders (SRAD) in adults with intellectual and developmental disabilities (IDD) and compare the sociodemographic and clinical characteristics of adults with IDD and SRAD to those with IDD or SRAD only.DesignPopulation-based cohort study (the Health Care Access Research and Development Disabilities (H-CARDD) cohort).SettingAll legal residents of Ontario, Canada.Participants66 484 adults, aged 18–64, with IDD identified through linked provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 24 publications
5
28
0
2
Order By: Relevance
“…Validated algorithms for these conditions were used in the current study (Gershon et al 2009 ; Hux et al 2002 ; Quan et al 2009 ). The look-back period for diabetes, hypertension, asthma, psychiatric disorders, and substance-related and addictive disorders was 2 years (2007–2009; Lin et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Validated algorithms for these conditions were used in the current study (Gershon et al 2009 ; Hux et al 2002 ; Quan et al 2009 ). The look-back period for diabetes, hypertension, asthma, psychiatric disorders, and substance-related and addictive disorders was 2 years (2007–2009; Lin et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…This premise is enshrined in the Equality Act () but also has been the cornerstone of government policy which strongly advocates the use of universal health services by people with intellectual disability (Department of Health, , ). Recent studies have shown that people with intellectual disability are vulnerable to a number of mental health conditions such as common mental disorders, psychosis and dementia (Cooper, Smiley, Morrison, Williamson, & Allan, ; Lin et al., ) as well as substance use disorders (Van Duijvenbode et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the sparse literature regarding substance misuse in people with intellectual disability there is increasing interest in studying such problems because most people with intellectual disability now live in the community and are likely to be exposed to substances in their social networks as well as consuming them (Lin et al., ; Miller & Whicher, ). UK and USA population‐based studies indicate that the prevalence of substance misuse in people with intellectual disability ranges from 0.5% to 2.5% and may be as high as 22.5% for any substance in clinical samples (Cooper et al., ; Hassiotis et al., ; McGillicuddy & Blane, ; Pezzoni & Kouimtsidis, ; Sturmey, Reyer, Lee, & Robek, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same trends are already occurring in developed countries, with rising risk and prevalence of substance abuse among ID people. [ 8 9 ] Currently, the prevalence and risk for substance use and abuse among ID people in India are unknown, highlighting the need for efforts to identify and map the epidemiological profiles of the behavior and the indicated correlated conditions early.…”
mentioning
confidence: 99%